Fostering Communication through Blogs in an International, Multi-grade Context - Andrea Castellanos (Asociación Colombiana de Profesores de Ingles, 2009)
This is a report on a pedagogical application carried out in a bilingual (Spanish-English), Colombian school in connection with a Canadian and a Chilean one through an online platform hosted by the Francisco José de Caldas University. The different tasks developed intended to show the importance of networking for educational purposes and the place of new technologies in students' learning processes. As a result, this pedagogical intervention enhanced the use of English as a foreign language. Besides, the use of technology raised students' awareness about the cultural differences through contact with other learners of their same or similar age when sharing their thoughts, expectations, questions and answers about topics of common interest.